Evolution of coronal magnetic field parameters during X5.4 solar flare - Garland, Seth H.; Yurchyshyn, Vasyl B.; Loper, Robert D.; Akers, Benjamin F.; Emmons, Daniel J. (Frontiers in Astronomy and Space Sciences, 2023)
The coronal magnetic field over NOAA Active Region 11429 during a X5.4 solar flare on 7 March 2012 is modeled using optimization based Non-Linear Force-Free Field extrapolation. Specifically, 3D magnetic fields were modeled for 11 timesteps using the 12-minute cadence Solar Dynamics Observatory (SDO) Helioseismic and Magnetic Imager photospheric vector magnetic field data, spanning a time period of one hour before through one hour after the start of the flare. Using the modeled coronal magnetic field data, 7 different magnetic field parameters were calculated for 3 separate regions: areas with surface |Bz| greater than or equal to 300 G, areas of flare brightening seen in SDO Atmospheric Imaging Assembly imagery, and areas with surface |B| greater than or equal to 1000 G and high twist. Time series of the magnetic field parameters were analyzed to investigate the evolution of the coronal field during the solar flare event and discern pre-eruptive signatures. The data shows that areas with |B| greater than or equal to 1000 G and |Tw| greater than or equal to 1.5 align well with areas of initial flare brightening during the pre-flare phase and at the beginning of the eruptive phase of the flare, suggesting that measurements of the photospheric magnetic field strength and twist can be used to predict the flare location within an active region if triggered. Additionally, the evolution of 7 investigated magnetic field parameters indicated a destabilizing magnetic field structure that could likely erupt.